Method of choosing vectors for investment strategies implementation - Baydala, N.; Kniaz, S.; Pauk, O. (Національний університет "Львівська політехніка", 2013)
Statement of the problem. In market conditions, the investment activity of enterprises requires diversification of objects and methods of investment. This helps to minimize investment risks, stabilize cash flows in space and time, as well as to increase the guarantee of successful implementation of investment to the entities, which take indirect participation in investment processes. The problem consists in the absence of scientifically grounded methodological regulations regarding the selection of methods of the investment strategies implementation. Consequently, most of the investment decisions are based on an intuitive approach which reduces the possibility of opportuneness and completion in the implementation of purposes established by investors’.
Keywords: strategies; investment strategies